Kinerja Badan Usaha Milik Desa (BUMDes) Di Desa Sukamakmur Kecamatan Tolangohula Kabupaten Gorontalo - Oktaviani Bouti; Rustam Tohopi; Alfiyah Agussalim (Transbahasa, 2025)
This Research aims to analyze the performance of Village-Owned Enterprises (BUMDes) in Sukamakmur Village, Tolangohula Subdistrict, Gorontalo Regency, focusing on five key indicators: work quality, responsibility, cooperation, and initiative. A qualitative approach with a descriptive method was employed, and data were collected through interviews, observatons, and documentation involving BUMDes management, village officials, and supervisory bodies. The findings reveal that the work quality and quantity of the BUMDes management remain suboptimal, as evidenced by inadequate management of business units and inconsistent task execution. While the sense of responsibility among management is relatively strong, challenges remain in terms of transparency and accountability. Cooperation among management members and with village authorities is assessed as satisfactory, though public participation remains limited. Meanwhile, the initiative of the management in developing ideas and solutions remains low, hindering the optimal development of BUMDes enterprises. This research emphasizes the importance of enhancing management capacity strengthening coordination, and empowering the community to enable BUMDes to function more effectively as a driver of the village economy.